2012
DOI: 10.1109/tgrs.2012.2202122
|View full text |Cite
|
Sign up to set email alerts
|

Fengyun-3B MicroWave Humidity Sounder (MWHS) Data Noise Characterization and Filtering Using Principle Component Analysis

Abstract: MicroWave Humidity Sounder (MWHS) onboard both Fengyun-3A (FY-3A) and FY-3B satellites have three channels (channels 3-5) near the 183-GHz water-vapor absorption line. These channel frequencies are also used in other instruments such as Advanced Microwave Sounding Unit-B (AMSU-B) and Microwave Humidity Sounder (MHS) onboard MetOp and NOAA satellites. Both MWHS and MHS are cross-track scanners.In this paper, a comparison between the simulated brightness temperatures with MWHS measurements clearly shows that MWH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…A new technique has been developed through a combination of PCA and EEMD methods to characterize the scan dependence in brightness temperature observations and to separate the weather signals from the striping noise when present. For the purpose of this study, we will assume that the first PC mode (i.e., the first eigenvector) captures most of the scan‐dependent features of cross‐track radiometer measurements [ Zou et al ., ] and the remaining PC modes describe the atmospheric signals. Also, by assuming the striping noise is constant in the cross‐track direction, the striping noise is contained in the PC coefficients corresponding to the first PC mode.…”
Section: A Striping Analysis Methods For Earth Scene Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A new technique has been developed through a combination of PCA and EEMD methods to characterize the scan dependence in brightness temperature observations and to separate the weather signals from the striping noise when present. For the purpose of this study, we will assume that the first PC mode (i.e., the first eigenvector) captures most of the scan‐dependent features of cross‐track radiometer measurements [ Zou et al ., ] and the remaining PC modes describe the atmospheric signals. Also, by assuming the striping noise is constant in the cross‐track direction, the striping noise is contained in the PC coefficients corresponding to the first PC mode.…”
Section: A Striping Analysis Methods For Earth Scene Observationsmentioning
confidence: 99%
“…The PCA method was also used in Zou et al . [] to identify a scan angle‐dependent cohesive noise along the instrument scan line of Microwave Humidity Sounder (MWHS) on board Chinese Fengyun‐3A (FY‐3A) and FY‐3B satellites. A method used to extract random noise in an along‐track varying PC coefficient is the Ensemble Empirical Mode Decomposition (EEMD) [ Huang and Wu , ; Wu and Huang , ; Wu et al ., ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MWHS makes 98 measurements across a scan line from −53.35 • to +53.35 • at about 1.1 • increment with the resolution of 15 km at nadir. Several studies based on the MWRI or the MWHS observations can be found in the literature [25]- [27].…”
Section: Datamentioning
confidence: 99%
“…The Earth's atmosphere can be observed more frequently than without Chinese satellites. A preliminary evaluation of instrument performance through a comparison with data from NOAA, MetOp, and the NASA Aqua satellite data revealed that data from MWTS, MWHS, and MWRI were of good quality (Guan et al, 2011;Yang et al, 2011;Zou et al, 2012a;Zou et al, 2012b;Zou et al, 2012c). In this study, we investigated the polarization differences of measurements between two MWHS window channels and investigated the potential value for satellite data assimilation and calibration.…”
Section: Introductionmentioning
confidence: 99%